2015
DOI: 10.1890/14-2022.1
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in dynamic regime of an invasive lady beetle are linked to the invasion and insecticidal management of its prey

Abstract: The spread and impact of invasive species may vary over time in relation to changes in the species itself, the biological community of which it is part, or external controls on the system. We investigate whether there have been changes in dynamic regimes over the last 20 years of two invasive species in the midwestern United States, the multicolored Asian lady beetle Harmonia axyridis and the soybean aphid Aphis glycines. We show by model selection that after its 1993 invasion into the American Midwest, the ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 84 publications
1
39
0
Order By: Relevance
“…Coleomegilla maculata (DeGeer) (Coccinellidae) (Bahlai et al 2015). However, this last study also 266 noted that declines of several species reported previously from the same site (Colunga-Garcia, Gage 267 1998) appear to have stabilized or reversed, having become statistically undetectable (Bahlai et al 268 2015).…”
Section: Harmonia Axyridis and Declines Of Native Ladybirds 255 256mentioning
confidence: 66%
“…Coleomegilla maculata (DeGeer) (Coccinellidae) (Bahlai et al 2015). However, this last study also 266 noted that declines of several species reported previously from the same site (Colunga-Garcia, Gage 267 1998) appear to have stabilized or reversed, having become statistically undetectable (Bahlai et al 268 2015).…”
Section: Harmonia Axyridis and Declines Of Native Ladybirds 255 256mentioning
confidence: 66%
“…In this year, native species tended to increase in abundance to values similar to those in 2010 and 2011. Similar trends have been observed in Michigan where previous reports of declines of several species of native coccinellids are no longer observed (Bahlai et al ., ). Long‐term monitoring is critical to derive robust distribution and population trends for coccinellids, and this in turn will enable assessment of when the loss of biodiversity in coccinellid assemblages may have serious consequences for biological control.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study, analyzing data from the initial phase of soybean aphid colonization of North America, found that high‐aphid and low‐aphid years often alternated, resulting in an approximately even chance that a given year will be a high‐aphid year. Since the initial invasion, a combination of increased insecticide applications and predation by the predacious ladybird beetle Harmonia axyridis have resulted in a loss of this trend . In fact, correlative data analysis by Bahlai et al .…”
Section: Discussionmentioning
confidence: 99%